Navigating the Cultures of Health Care and Health Insurance Highly skilled migrants in the US - Zeldes, Nina (Culture and Health, 2023)
What are the barriers preventing migrants from accessing and successfully utilizing health care in their new home country? Do these barriers vary across different migrant origin countries? And are they still a problem for highly skilled migrants, who often have well-paid jobs and health insurance provided by their employers? Based on field research conducted in the Washington D.C. area, Navigating the Cultures of Health Care and Health Insurance takes a mixed methods, qualitative and quantitative approach to the study of foreign patients' utilization and assessment of health care in the US. Through interviews with both health care providers and patients, attitudes towards US health insurance and medical treatment are compared for migrants from three countries with very different cultural backgrounds and health insurance systems: Germany, India and Japan. Combined with an in-depth literature review, historical and contemporary surveys of health care across countries and analysis of health-related terms in the media, the results of this research indicate that foreign patients' barriers to good health care persist despite access to health care services and insurance coverage, and reveal recurring transnational care seeking patterns, such as bringing medicines from abroad, delaying treatment for medical visits, insurance juggling and more. By describing their difficulties in integrating into the US health care system, the migrants in this study show the challenges and the potential for improvements in providing the care that migrants need in their new home.